Design and 3D printing of reconfigurable structures - Ng, Garvin Chong Hou (2017)
This purpose of this project is to research into possible reconfigurable 3D structure which can be designed and 3D printed. The focus identified is to design an aerofoil structure that can change from one stable shape to another stable shape using the bistable structure and compliance joint concept. The aim of the aerofoil shape change is to reduce the overall drag produced by the wing structure during an aircraft cruising. This report will cover the different design concept developed over the course of this project which ultimately leads to the final aerofoil design concept which can reduce the overall maximum thickness by approximately 8.1%. The reduction in the maximum thickness is deemed to reduce the drag coefficient of the wing structure leading a reduction in the total drag produced by an aerofoil structure.